(untitled) (World Bulletin of Social Sciences, 2023)
The article discusses the theoretical basis for the use of multimedia vocabulary in the formation of oral and written speech in students in native language classes, its specific advantages. In addition, the use of different texts in native language classes and the role of the text in the formation of the student’s speech culture were discussed